An experimental and numerical study of the microstructural and biomechanical properties of human peripheral nerve endoneurium for the design of tissue scaffolds - Yan, Liwei; Entezari, Ali; Zhang, Zhongpu; Zhong, Jingxiao; Liang, Jing; Li, Qing; Qi, Jian (Frontiers in Bioengineering and Biotechnology, 2022)
Biomimetic design of scaffold architectures represents a promising strategy to enable the repair of tissue defects. Natural endoneurium extracellular matrix (eECM) exhibits a sophisticated microstructure and remarkable microenvironments conducive for guiding neurite regeneration. Therefore, the analysis of eECM is helpful to the design of bionic scaffold. Unfortunately, a fundamental lack of understanding of the microstructural characteristics and biomechanical properties of the human peripheral nerve eECM exists. In this study, we used microscopic computed tomography (micro-CT) to reconstruct a three-dimensional (3D) eECM model sourced from mixed nerves. The tensile strength and effective modulus of human fresh nerve fascicles were characterized experimentally. Permeability was calculated from a computational fluid dynamic (CFD) simulation of the 3D eECM model. Fluid flow of acellular nerve fascicles was tested experimentally to validate the permeability results obtained from CFD simulations. The key microstructural parameters, such as porosity is 35.5±1.7%, tortuosity in endoneurium (X axis is 1.26±0.028, Y axis is 1.26±0.020 and Z axis is 1.17±0.03, respectively), tortuosity in pore (X axis is 1.50±0.09, Y axis is 1.44±0.06 and Z axis is 1.13±0.04, respectively), surface area-to-volume ratio (SAVR) is 0.165±0.007 μm-1 and pore size is 11.8±2.8 μm, respectively. These were characterized from the 3D eECM model and may exert different effects on the stiffness and permeability. The 3D microstructure of natural peripheral nerve eECM exhibits relatively lower permeability (3.10x10-12) than other soft tissues. These key microstructural and biomechanical parameters may play an important role in the design and fabrication of intraluminal guidance scaffolds to replace natural eECM. Our findings can aid the development of regenerative therapies and help improve scaffold design.